IMPLEMENTASI KONSEP PENDIDIKAN PESANTREN DI SEKOLAH ISLAM TERPADU AL-FURQON PALEMBANG - Agung Mandala Putra; Fajri Ismail; Muhammad Win Afgani (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
This study discusses the implementation of the concept of Islamic boarding school education in the SIT Al-Furqon Palembang dormitory. The problems studied were the form of the applied pesantren education concept, the process of implementing the applied pesantren education concept, and the supporting and inhibiting factors. The research method uses qualitative methods. The research informants were leaders and teachers in the SIT Al-Furqon Palembang dormitory, totaling six people. Collecting data using observation, interviews and documentation. Data analysis using qualitative analysis. The results of the study show that the educational concept applied in the SIT Al-Furqon Palembang hostel includes curriculum, educational process and facilities and mission and vision. The pesantren curriculum can be identified from the hostel activities and subjects. The educational process can be seen from the aspects of teaching and learning activities, methods and atmosphere of the hostel. The implementation of the concept of Islamic boarding school education is carried out at the Al-Furqon hostel which can be seen from every activity of the hostel, through the activities of direction, guidance, communication, coordination and motivation to maintain the characteristics of the hostel as an integrated Islamic school based on Islamic boarding schools. Factors that support the implementation of the concept of Islamic boarding school education include, curriculum, the role of the founder, human resource support, and adequate infrastructure. The inhibiting factors are some undisciplined students, unmaintained facilities and insufficient funds for funding. But the inhibiting factors are not a significant obstacle.